MENTAL HEALTH AND QUALITY OF LIFE IN PATIENTS WITH CARDIOVASCULAR DISEASES: SOCIAL SUPPORT AS MEDIATOR - Shafiq, Sameera; Iqra Shahzadi (Journal of Postgraduate Medical Institute, 2023)
Objective: To investigate the relationship between mental health, quality of life social support in patients with cardiovascular diseases, and mediating role of social support between these variables. Methodology: This cross-sectional, correlational study was conducted between February and May 2020. Data was collected with purposive sampling from 180 participants (70.6% males and 29.4% females) with an age range of 17 to 83 years (M = 57.74, SD = 13.02) who had been suffering from cardiovascular diseases. An informed consent form, demographic sheet, and Urdu versions of the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS), Multidimensional Scale of Perceived Social Support (MSPSS), Depression Anxiety Stress Scale-21 (DASS-21), and WHOQOL-BREF were used. Results: The quality of life is perceived as average by the majority of them (48.9%). A significant negative relationship was found between depression (r = -0.43, p<0.01), anxiety (r = -0.28, p<0.01), and stress (r = -0.33, p<0.01) with social support. Wellbeing has also been found to be significantly and negatively correlated with depression (r= -0.57, p<0.01), anxiety (r = -0.37, p<0.01), and stress (r = -0.39, p<0.01). There is also a significant mediating effect of social support on depression, anxiety, stress, and well-being in the quality of life of patients with cardiovascular diseases. Conclusion: Patients with cardiovascular diseases have poor mental health and perceived low to average quality of life. Social support is a full mediator (B = -.35, p = .01) for anxiety and partial mediator (B = .35, p < 0.01), for depression, stress, and wellbeing with quality of life.